2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090177
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea prediction during wakefulness

Abstract: In this paper, a novel technique based on signal processing of breath sounds during wakefulness for prediction of obstructive sleep apnea (OSA) is proposed. We recorded tracheal breath sounds of 35 people with various severity of OSA and 17 non-apneic individuals; the breath sounds were recorded in supine and upright positions during both nose and mouth breathing at medium flow rate. Power spectrum, Kurtosis and Katz fractal dimension of the recorded signals in every posture and breathing maneuver were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[ 31 ] showed that severe OSA patients could be identified during wakefulness by using a combination of patient anthropometric parameters and tracheal sound information. M ontazeri and M oussavi [ 32 ] used tracheal sounds to screen for OSA during wakefulness. Extracted spectral features of the tracheal sounds showed characteristics that could easily discriminate OSA patients from control subjects.…”
Section: Clinical Applications For Sleep Studiesmentioning
confidence: 99%
“…[ 31 ] showed that severe OSA patients could be identified during wakefulness by using a combination of patient anthropometric parameters and tracheal sound information. M ontazeri and M oussavi [ 32 ] used tracheal sounds to screen for OSA during wakefulness. Extracted spectral features of the tracheal sounds showed characteristics that could easily discriminate OSA patients from control subjects.…”
Section: Clinical Applications For Sleep Studiesmentioning
confidence: 99%